Gas exchange in maize as a function of aeration porosity in a cohesive soil - Marques, Edilaine; Mota, Jaedson Cláudio; de Lacerda, Claudivan; da Silva, Francisca; Romero, Ricardo (Revista Ciência Agronômica, 2021)
Due to their physical characteristics, cohesive soils of either low or high aeration porosity can intensify limitations on plant cultivation. With the hypothesis that moist cohesive horizons where the soil has not yet reached a hard to extremely hard consistency may present a level of aeration porosity that affects gas exchange in maize plants, the aim of this study was to understand the influence of a cohesive horizon at different levels of aeration porosity on gas exchange in maize. The experiment was conducted in Fortaleza in the state of Ceará in a screened and covered environment, in a completely randomised block design with five levels of aeration porosity (AP) (0.04, 0.06, 0.09, 0.11 and 0.13 m3 m-3) and six replications, giving a total of 30 experimental units. The variables under analysis were intrinsic permeability (Kair) and gas exchange. Increases in AP afforded an increase in Kair. The AP of 0.04 and 0.13 m3 m-3 reflected in lower values for the photosynthetic rate (A) (24.54 and 25.50 μmol CO2 m2 s-1 respectively) and internal CO2 concentration (140.72 and 118.66 µmol mol-1 respectively). With the increase in AP, stomatal conductance and transpiration were reduced by 18% and 13.6% respectively, while the increase in instantaneous carboxylation efficiency was 19%, and intrinsic water use efficiency, 21%. It was concluded that variations in aeration porosity in cohesive soils affected gas exchange in maize plants. The AP of 0.04 and 0.13 m3 m-3 reduced the value of A due to non-stomatal and stomatal limitations respectively.